Evaluasi Instalasi Pengolahan Air Minum Unit Sukaraja Perumda Tirta Sukapura Kabupaten Tasikmalaya - Ihsan Faturahman; Mohamad Rangga Sururi (Jurnal Serambi Engineering, 2024)
Sukaraja Unit is a Water Treatment Plant (WTP) with a treatment capacity of 20 litres/second, Sukaraja WTP is operated by Perumda Tirta Sukapura Tasikmalaya Regency which was established in 1975 based on the legal basis of Regional Regulation of Tasikmalaya Regency Level II No. 7 of 1975 which is still in operation. The main concern is the water quality of the Ciwulan River and the produced water from the Sukaraja Water Treatment Plant (WTP). This assessment is based on design criteria from literature and applicable regulations, which are compared with water quality, water quantity, water continuity and WTP performance assessment based on existing data or secondary data. The raw water quality recorded several parameters that did not meet the quality standards and the dimensions of the treatment plant were not based on the design criteria. The basis of the existing problems is caused by the unsuitability of the operating system of the Sukaraja Water Treatment Plant. Water quality problems are caused by various activities in the area around the Ciwulan River, such as domestic waste disposal and the use of the river for agricultural irrigation. Improving the operating system of the Sukaraja Water Treatment Plant, repairing any damaged WWTP, and recommending unit dimensions that meet design criteria are suggestions that can be given from these problems.